Two-gap superconductivity in heavily n-doped graphene: Ab initio Migdal-Eliashberg theory - Margine, E; Giustino, F (American Physical Society, 2014)
Graphene is the only member of the carbon family from zero- to three-dimensional materials for which superconductivity has not been observed yet. At this time, it is not clear whether the quest for superconducting graphene is hindered by technical challenges, or else by the fluctuation of the order parameter in two dimensions. In this area, ab initio calculations are useful to guide experimental efforts by narrowing down the search space. In this spirit, we investigate from first principles the possibility of inducing superconductivity in doped graphene using the fully anisotropic Migdal-Eliashberg theory powered by Wannier-Fourier interpolation. To address a best-case scenario, we consider both electron and hole doping at high carrier densities so as to align the Fermi level to a van Hove singularity. In these conditions, we find superconducting gaps of s-wave symmetry, with a slight anisotropy induced by the trigonal warping, and, in the case of n-doped graphene, an unexpected two-gap structure reminiscent of MgB2. Our Migdal-Eliashberg calculations suggest that the observation of superconductivity at low temperature should be possible for n-doped graphene at carrier densities exceeding 1015c 2. © 2014 American Physical Society.